UPAYA PEMERINTAH DESA MENDORONG PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DI DESA WANA BAKTI KECAMATAN KETUNGAU TENGAH KABUPATEN SINTANG - Antonius Erwandi (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2018)
The lower level of community participation today is because in the development the village government has managed its finances autonomously in the form of a Village Fund Budget (ADD) so that development is generally financed from ADD in addition to project development patterns without involving the community. The research method used is a qualitative descriptive approach, the data analysis technique is qualitative, the tools used are the Observation Guide, interview guide and documentation. The research subjects were 8 people, namely the Village Head, BPD Chairperson, 5 Village Adat Village and Community Chairpersons. The results of the study showed that the form of community participation in the form of proposals was only delivered at the village development planning meeting. The motivation of the community in involvement is very low, namely as wage workers in the implementation of development project work by the village government and has never been done in mutual cooperation or in the form of community self-help. Human resources in the village government are in accordance with the standards of equivalent high school education, whereas as in Law Number 6 of 2014, they do not yet have an understanding in mobilizing local communities to participate in the development system.